Does functional strength training program improve ice speed and agility in young elite ice hockey players? Functional strength training`s impact on hockey performance - Bieniec, A.; Grabara, M. (Frontiers in Physiology, 2025)
Purpose: The aim of this study was to investigate the effects of a functional strength training (FST) program on ice speed and agility in young elite male ice hockey players.